Pergeseran Pola Komunikasi Pedagang dan Konsumen dalam Menghadapi Fenomena Penurunan Minat Belanja di Pasar Aceh - Salwatun Hasanah; Asmaunizar Asmaunizar; Fitri Meliya Sari (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Based on the overall findings of the study, it can be concluded that the decline in shopping interest in Pasar Aceh is not solely due to changes in the lifestyle of modern society, but reflects a fundamental transformation in the way consumers interpret the shopping experience. Consumers are now increasingly considering the aspects of convenience, time efficiency, access to information, and quality of communication in making choices, so traders are required to adapt to these dynamics. Merchants who previously relied only on direct interaction are beginning to understand the importance of communication strategies that are more persuasive, informative, and oriented to consumer needs. The use of digital technology such as WhatsApp, Facebook Marketplace, and Instagram has proven to open up new opportunities to expand the reach of promotions, facilitate transactions, and maintain relationships with customers through faster and more flexible communication. Nonetheless, the social values typical of traditional markets, such as friendliness, familiarity, and trust-based relationships, remain a major force that cannot be completely replaced by technology. In fact, the combination of a humanist social approach and digital innovation is an effective strategy for traders in dealing with increasingly modern, selective, and critical consumer behavior. Thus, the sustainability of the Aceh Market is not only determined by the ability to adopt technology, but also by efforts to maintain the social identity of the market. Therefore, continuous support from the government, market managers, and traders is needed to improve service quality, modernize facilities, and strengthen digital capacity so that the Aceh Market remains relevant and able to compete in the midst of an ever-growing economic transformation.